Opinie słuchaczy studiów podyplomowych na temat nauczania na odległość - Lewicka-Zelent, Agnieszka (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Zmiany cywilizacyjne wymuszają modyfikacje w wielu sferach funkcjonowania człowieka, w tym w tej dotyczącej edukacji. Tradycyjne metody nauczania coraz częściej wypierane są przez nowoczesne technologie informatyczno-komunikacyjne. Coraz większą przychylność zyskuje nauczanie na odległość, które wydaje się tym bardziej cenne w przypadku osób pracujących, a pragnących doskonalić swoje umiejętności nabyte podczas studiów. Dlatego celem badania własnego było poznanie opinii słuchaczy studiów podyplomowych na temat kształcenia online. Przebadano 60 słuchaczy kończących naukę. Wypowiedzieli się oni na temat tego, jakie zalety i mankamenty dostrzegają w takiej metodzie nauczania.

Civilizational changes induce alterations in many spheres of human functioning, including the one relating to education. Traditional teaching methods are being increasingly replaced by modern information and communication technologies. Distance education is becoming greatly favoured, as it is valuable especially for working individuals who desire to improve their abilities acquired during the studies. Therefore, the aim of author’s own research was to find out the opinions of post-graduate students about e-learning. Sixty (60) students currently finishing their studies have been examined. They expressed their opinions on advantages and shortcomings of such an educational method.
Opinions of Post-Graduate Students on Distance Education
Keywords: nauczanie na odległość; student; studia podyplomowe; zalety; wady; distance education; student; post-graduate study; advantages disadvantages